Prospects for the world economy - Sylos Labini, Paolo (PSL Quarterly Review, 2012)
Analysis here is founded on certain analogies with the Great Depression of the Thirties and four fundamental points: innovations, changes in the market forms, changes in income distribution and the sustainability of debts. The duration of prosperity depends first of all on the importance and variety of investment opportunities opened up by them, whereas crisis duration is conditioned by the size of indebtedness. The central problem in America today is precisely that of the sustainability of debts, to evaluate which criteria are studied in this paper. Full recovery will only be possible once past the stage in which firms and families contract debts primarily to repay other debts falling due and avoid bankruptcy. Proof that debts have fully reacquired the function of supporting growth will be given by the recovery of investments. In any case, the crisis is unlikely to reach the gravity of the Great Depression not only because a price fall is to excluded, but also because repetition of the mistakes in monetary policy are to be ruled out. JEL Codes: D14, E66, H63